A Volumetric Assessment Using Computed Tomography of Canine and First Molar Roots in Dogs of Varying Weight. (June 2018) - Scherer, Ellen; Snyder, Christopher J.; Malberg, Jessica; Rigby, Brittney; Hetzel, Scott; Waller, Ken
Mandibular volume and tooth root volumes were shown to increase at different rates at locations containing the roots of the canine (C) and mesial and distal roots of the first molar (M1). Thirty-six dogs were included in this study. Data were generated using computed tomography at locations of the mandible involving the roots of the C and M1 teeth. Software was used to trace the external surface of the mandible, calculating the volume of the mandible at each location. Similar techniques were used to trace and calculate the volume of the C and M1 roots. Mandible volume, tooth root volume, and root percentage of mandible volume were analyzed and compared using the slopes of the best fit line. At the M1 mesial and distal roots, mandible volume ( P < .001) and root volume ( P < .001) were both noted to increase, with increasing weight at different rates. The rate of change in the root percentage by weight of M1 roots was not different ( P = .214). Each location demonstrated a different increasing rate of change for mandibular volume and increasing root volume. Results show that as patient's weight increases, the mandible and root volumes increase at different rates. Root percentage by volume at all three locations was noted to decrease by the same rate. Canine and M1 roots are proportionally larger than the supporting mandibular bone in smaller patients. Care should be taken to recommend periodontal disease prevention for owners of small dogs and consideration made when performing extractions or other surgery that may destabilize the mandible.